PENERAPAN PROGRAM SEKOLAH RAMAH ANAK DALAM PEMBENTUKAN KARAKTER POSITIF PADA ANAK - Titien Ruswanti; Miftakhul Jannah; Yes Matheus Lasarus Malaikosa (CV. ADIBA AISHA AMIRA, 2024)
A child-friendly school is an educational institution designed to provide a safe, clean, healthy, and caring environment for children's needs and rights. This article analyzes the concept of child-friendly schools in shaping positive character in early childhood. Using a literature review method, this study explores information from national and international journals. The results show that the implementation of child-friendly schools includes comprehensive fulfillment of children's rights, character development through the cultivation of moral values, and enjoyable learning methods suitable for children's development. The implementation stages include preparation, planning, implementation, as well as monitoring and evaluation. Child-friendly schools are expected to create a conducive learning environment, support the social, emotional, and academic development of children, and produce future generations with good character. With a friendly and loving approach, child- friendly schools can meet the needs and rights of children comprehensively, create an inclusive educational environment, and produce individuals ready to face challenges in the future.